Regulation of early gene expression from the bovine papillomavirus genome in transiently transfected C127 cells. - Szymanski, P (1991)
Expression of bovine papillomavirus (BPV) early gene products is required for viral DNA replication and establishment of the transformed phenotype. By the use of a highly efficient electroporation system, we have examined for the first time the transcriptional activity of BPV promoters in their natural genomic context in a replication-permissive cell line. We have determined that a qualitatively distinct stage of transcription is not detectable prior to DNA replication in transiently transfected cells. This suggests that the transcriptional activity of the BPV genome in stably transformed cells represents the early stage of BPV gene expression. Quantitative differences in promoter activity between transiently transfected and stably transformed cells suggest that subtle changes in gene expression may control progression of the viral life cycle. Deletion analysis demonstrated that the E2 transactivator protein stimulates all of the early promoters through sequences located in the upstream regulatory region. This E2-dependent enhancer was found to be highly redundant, and particular E2 binding sites did not display a preference for particular promoters. Despite this dependence on a common cis-acting sequence, the various promoters displayed different sensitivities to the E2 transactivator. The findings that E2 regulates all promoters and, with the exception of the E2 repressors, that no other known viral gene product appears to affect transcription indicate that the E2 system functions as the master regulator of BPV early gene expression.